Bureaucrat Image in Russia - FROLOVA, Elena Victorovna; RYABOVA, Tatyana Mikhailovna; ROGACH, Olga Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The issue of a civil servant positive image development becomes a relevant one within the current terms of public confidence increase in civil service institution, the fight against corruption and state authority competence improvement. On the basis of public servant and citizen sociological survey about the professional and personal qualities of public servants, as well as on mass media content analysis, the authors describe a perfect portrait of a modern civil servant in Russia, determine the areas of his image transformation, and the factors of a positive image development. In the course of periodical context analysis the hypothesis was disproved that mass media develop a negative image of civil servants, which influences the negative perception of public servant activity by society. The sociological survey among officials and citizens showed that the opinion about civil servants in the minds of people is developed on the basis of the following factors:  the understanding that the employees work in accordance with the principle of serving for society and the state; the level of professionalism and competence among civil servants; the improvement of their work quality. Among the professional qualities, essential for officials were they specified ‘professionalism’ and ‘the ability to communicate with people’ and ‘activity’, ‘the spirit of enterprise’ and ‘integrity’ are specified among personal qualities. According to the author research results the factors that have a negative impact on the generated image of the public service were specified: a well-established negative stereotype of an official in people's minds; corruption; impunity; impaired communication.